2014
DOI: 10.3748/wjg.v20.i42.15518
|View full text |Cite
|
Sign up to set email alerts
|

Gut-liver axis and probiotics: Their role in non-alcoholic fatty liver disease

Abstract: The incidence of obesity and its related conditions, including non-alcoholic fatty liver disease (NAFLD), has dramatically increased in all age groups worldwide. Given the health consequences of these conditions, and the subsequent economic burden on healthcare systems, their prevention and treatment have become major priorities. Because standard dietary and lifestyle changes and pathogenically-oriented therapies (e.g., antioxidants, oral hypoglycemic agents, and lipid-lowering agents) often fail due to poor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
136
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 173 publications
(148 citation statements)
references
References 97 publications
0
136
0
5
Order By: Relevance
“…Additionally, in a subset of individuals, chronic NASH leads to hepatocellular carcinoma (HCC) [912]. NAFLD is rapidly becoming the most common cause of chronic liver injury in industrialized countries, in parallel with the increased consumption of a high fat, “Western-style” diet (HFWD) [3,4]. Dietary caloric restriction to reduce steatosis is a mainstay of NAFLD prevention, but its efficacy is hampered by poor compliance and potentially by early life metabolic and gut microbial alterations that have prolonged inhibitory effects on weight loss [4].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in a subset of individuals, chronic NASH leads to hepatocellular carcinoma (HCC) [912]. NAFLD is rapidly becoming the most common cause of chronic liver injury in industrialized countries, in parallel with the increased consumption of a high fat, “Western-style” diet (HFWD) [3,4]. Dietary caloric restriction to reduce steatosis is a mainstay of NAFLD prevention, but its efficacy is hampered by poor compliance and potentially by early life metabolic and gut microbial alterations that have prolonged inhibitory effects on weight loss [4].…”
Section: Introductionmentioning
confidence: 99%
“…Here, through feeding a WSD, early metabolic as well as molecular changes associated with the development of NASH (e.g., steatosis, inflammation, and insulin resistance) were induced in mice. Chronic intakes of this WSD promote pathological changes in the liver as well as at the level of intestine, which are also found in many humans with early NASH [for an overview of alterations, see also (20)(21)(22)]. Of course, despite many similarities with the human situation, it needs to be emphasized that the chronic intake in mice of a pair-fed liquid diet containing 50% wt:wt fructose and 25 E% fat with 0.16% wt:wt cholesterol does not resemble all alterations found in humans with NAFLD (e.g., genetic predisposition, lack of physical inactivity).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that visceral adipose contributing to overall lipidome was secondary to that of other sources of the drainage into the hepatic portal system, for example, the gut. While this is by no means a novel suggestion in the field of NASH [5][6][7], the exact mechanism of this contribution has yet to be demonstrated.…”
mentioning
confidence: 87%